Perbandingan Luaran Pasien Level Of Care 3 yang Menggunakan Ventilator Sebelum dan Sesudah Operasional Ruang High Care Unit Di RSUP Dr. Sardjito Yogyakarta - Suryaman, Rifandi; Widodo, Untung; Sari, Djayanti (Jurnal Komplikasi Anestesi, 2021)
Background: Mortality rate in emergency department (ED) of Dr. Sardjito General Hospital did not achieve national target. Result of evaluation and analysis of this condition was established of High Care Unit for critical care management of patient in ED with the goal to decrease morbidity and mortality rate. Objective: To compare outcome such as mortality rate, MSOFA exit score, Length of Stay(LOS) in IMC, HCU, hospital and ventilator day at patients 3rd level of care (LOC) using ventilator before and after the implementation of HCU at the Dr. Sardjito General Hospital. Method: This research was an observational study using retrospective cohort analysis. Subjects had been collected from medical record included 198 meet the inclusion criteria; aged ≥18 years who were treated with critical illness with 3rd level of care (LOC) who used a ventilator in the HCU or IMC of RSUP dr.Sardjito. Exclusion criteria were patients with end-stage malignancies, patients with HIV / AIDS infections, patients with end-stage chronic disease and incomplete medical record. Result: Mortality rate in HCU (40.4%) and IMC (73.3%) with p = 0.000. MSOFA exit score in HCU (5.5) and IMC (7.4) with p= 0.001. HCU and IMC length of stay (LOS) showed no statistically signifcant difference. Hospital LOS in HCU (314.7) hours and IMC (210.6) hours with p = 0.000. Ventilator day in HCU (5.1) days and IMC (4.8) days and showed no statistically signifcant difference. Conclusion: Mortality rate and MSOFA exit score in HCU was lower than IMC. There was no significant difference between LOS in HCU and IMC. Hospital LOS in HCU group 314.7 hours and IMC group was 192.6 hours. Ventilator day in HCU group was 5.1 days and IMC group 4.8 days.